Preparação de vidros e vitrocerâmicas de óxidos de metais pesados contendo prata: propriedades ópticas, estruturais e eletroquímicas - Bregadiolli, Bruna A. [UNESP]; Souza, Ernesto R.; Sigoli, Fernando A.; Caiut, José M. A.; Alencar, Mônica A. S. [UNESP]; Benedetti, Assis V. [UNESP]; Nalin, Marcelo (Sociedade Brasileira de Química, 2012)
Silver containing heavy metal oxide glasses and glass ceramics of the system WO3-SbPO4-PbO-AgCl with different AgCl contents have been prepared and their thermal, structural and optical properties characterized. Glass ceramics containing metallic silver nanoparticles have been prepared by annealing glass samples at temperatures above the glass transition and analyzed by transmission electron microscopy and energy dispersive X-ray microanalysis. The presence of the metallic clusters has been also confirmed by the observation of a surface plasmon resonance band in the visible range. Cyclic voltammetric measurements indicated the presence of metallic silver into the glasses, even before to perform the thermal treatment.
Preparation of glasses and glass ceramics of heavy metal oxides containing silver: optical, structural and electrochemical properties
Keywords: glass; glassceramics; nanoparticles